A 1500 MPa grade corrosion-resistant stainless steel for hot-stamping forming automobile parts
Patent Information
- Application Number
- CN202510171871.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-02-17
AI Technical Summary
导致专利中成分、工艺规定宽泛,并没有明确描述如何通过成分调整达到具体力学性能、耐蚀性能最优化设计和低成本设计的目标
[0036] 1) The steel grade of the present invention not only has high strength, but also good corrosion resistance. Combined with the corresponding hot stamping forming process, it is suitable for manufacturing automotive structural parts, reinforcement parts, safety parts and other components, such as bumpers, B-pillar reinforcement parts, etc.
Smart Images

Figure CN120082815B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of development and application technology of martensitic stainless steel, and in particular to a 1500MPa grade corrosion-resistant stainless steel for hot stamping automotive parts. Background Technology
[0002] The use of hot-stamped ultra-high-strength steel in automotive parts is essential for achieving lightweighting and improved safety. The oxidation problem during the austenitization process of traditional 1500MPa hot-formed steel 22MnB5 is significant. Currently, approximately half of the hot-formed steel sheets used globally employ Al-Si coating to prevent oxidation and decarburization at high temperatures. However, Al-Si coating is expensive, and scaling can occur on the mold surface during hot forming, affecting mold life and increasing production costs. Furthermore, because carbon hot-stamped steels like 22MnB5 lack corrosion resistance, they require painting protection when made into automotive parts, increasing production steps and costs, while also causing environmental pollution.
[0003] In recent years, with the implementation of the Carbon Border Adjustment Mechanism (CBAM, also known as the EU Carbon Border Tax), the green transformation of the automotive industry has become urgent. In the future, international automotive industry associations will gradually begin to promote carbon labeling for products. Therefore, green and low-carbon automotive steel products are becoming an inevitable development trend in the automotive industry due to their market competitiveness. Stainless steel, with its low life-cycle cost (LCA), is receiving increasing attention from the automotive industry. Stainless steel car bodies and ultra-high-strength stainless steel structural components, serving as the car body frame, possess advantages such as high strength, corrosion resistance, and paint-free operation. This not only reduces the need for pickling, degreasing, phosphating, and painting processes in car body manufacturing, significantly lowering production costs and meeting green environmental protection requirements, but also ensures that stainless steel is 100% recyclable without degradation. It suffers from minimal metal loss during use, reducing environmental pollution caused by metal corrosion and deterioration. The overall life-cycle cost is lower, making it more environmentally friendly.
[0004] The application of stainless steel in hot stamping processes requires resolving the contradiction between corrosion resistance and high-strength mechanical properties. Austenitic stainless steel offers good corrosion resistance but has low tensile strength, which cannot meet the ultra-high strength requirements of hot stamping. Ordinary 1Cr... 13 2Cr 13 Martensitic stainless steel, through hot stamping, can only achieve a strength of 1300-1400 MPa, which cannot meet the requirements for ultra-high strength; 3Cr 13 4Cr 13While martensitic stainless steels can achieve strengths up to 1500 MPa through hot stamping, they lack sufficient toughness and plasticity, and have poor corrosion resistance, failing to meet the corrosion resistance requirements of green, low-carbon automotive parts. Ultra-high strength, high-toughness martensitic stainless steels used in aerospace and other applications can meet the ultra-high strength and corrosion resistance requirements of hot stamping, but these steels typically contain high levels of expensive alloying elements such as Cr, Ni, Mo, Co, and Ti, resulting in high costs and limiting their widespread application in automotive hot-stamped parts. PCT patent application number 201880011193.7 discloses a method for manufacturing parts by hot forming and its application. This method describes the steel used to manufacture parts using stainless steel and the intended use of the parts. The invention specifies the following components: C ≤ 0.2%, Si ≤ 3.5%, Mn 1.5%–16%, Cr 8%–14%, Ni ≤ 6%, N ≤ 1%, Nb ≤ 1.2%, Ti ≤ 1.2%, Mo ≤ 2.0%, V ≤ 0.15%, Cu ≤ 2.0%, Al ≤ 0.2%, and B ≤ 0.05%. This patent has an overly broad scope of protection, while the embodiments are only applicable to a limited range. The steel described in the patent can be used in vehicle transport components, high-strength collision safety rollover protection bars, or complex structural components such as pillars or fairings; even in anti-graffiti solutions, such as park benches and railway surfaces; and in tableware. This results in broad specifications for composition and processes in the patent, without clearly describing how to achieve optimized mechanical properties, corrosion resistance, and low-cost design through composition adjustments. Furthermore, the high content of alloying elements such as Mo, Nb, Mn, and Ti in the steel leads to high costs; corrosion resistance is also not specified.
[0005] In addition, there are currently few patents and articles reporting on ultra-high strength stainless steel for hot stamping in automobiles. Therefore, developing a low-cost, green, low-carbon, ultra-high strength, corrosion-resistant stainless steel to meet the needs of hot-stamped automotive parts has become a hot topic of competition among countries. Summary of the Invention
[0006] This invention provides a tensile strength of 1500 MPa or higher and a pitting potential ≥0.05V. SCE This new type of stainless steel is a hot-stamped stainless steel for automotive structural parts and welded components with excellent corrosion resistance. It features low cost, no plating required for environmental friendliness, ultra-high strength, good corrosion resistance, and high hardenability. It is suitable for large-scale industrial production of hot-rolled or cold-rolled sheets, and the hot-stamping process fully meets the requirements of current hot-forming production lines.
[0007] To achieve the above objectives, the present invention employs the following technical solution:
[0008] A 1500MPa grade corrosion-resistant stainless steel for hot-stamped automotive parts, the chemical composition of the steel by weight percentage is as follows: C: 0.05%~0.20%, Si: 0.05%~0.50%, Mn: 0.50%~2.00%, P≤0.020%, S≤0.010%, Cr: 12.0%~15.0%, V: 0.05%~0.15%, Nb: 0.02%~0.10%, Ni≤1.00%, Cu≤0.30%, Al<0.05%, N: 0.01%~0.10%, with the balance being Fe and unavoidable impurity elements such as Mg, O, Ca, etc.
[0009] The Cr equivalent in steel, Creq = Cr% + Mo% + 1.5 × Si% + 0.5 × Nb% + 5 × V% + 3Al, should be controlled within 15.0%.
[0010] The Ni equivalent in steel, Nieq = Ni% + 30 × C% + 0.5 × Mn% + 0.3 × Cu% + 25 N% + Co%, should be controlled at 8.0%.
[0011] The δ phase formation temperature in the steel is ≥1100℃, and the Nb (C, N) solution solution temperature is ≥1100℃.
[0012] Cr in steel 23 C6 and Cr x N y The solution temperature is ≤950℃.
[0013] The solidification temperature of V (C, N) in steel is ≥870℃.
[0014] The stainless steel plate has a tensile strength ≥1500MPa and a pitting potential ≥0.05V. SCE .
[0015] The roles and control ranges of various elements in the stainless steel of this invention are as follows:
[0016] 1) C is an austenite-forming element. Increasing the carbon (C) content can raise the δ-ferrite formation temperature and expand the austenite phase region. In this invention, to obtain high-strength stainless steel dominated by martensite, based on the Schaeffler phase diagram, the Ni equivalent (Nieq = Ni% + 30 × C% + 0.5 × Mn% + 0.3 × Cu% + 25 N% + Co%) is controlled within 8.0%. Simultaneously, considering cost factors, Ni is basically not added to this steel, while fully utilizing the austenite-forming effect of C. Furthermore, C is a Cr... 23 The higher the content of C6-forming elements, the higher the Cr content. 23The formation temperature of C6 decreases the concentration of dissolved Cr, severely reducing the corrosion resistance of stainless steel and negatively impacting its plasticity and weldability. Conversely, increasing the C content reduces the strength of stainless steel. Therefore, the selection of the C content must balance both corrosion resistance and mechanical properties. Based on thermodynamic calculations, the optimal range for C content is 0.05%–0.20%.
[0017] 2) Cr is the most important alloying element in stainless steel, playing a decisive role in corrosion resistance. Cr forms a dense Cr2O3 oxide film on the surface of stainless steel, which has a strong passivating effect, thus achieving corrosion resistance. In this invention, the formation of a dense Cr2O3 oxide film on the surface of stainless steel must be considered first, with the minimum Cr content in the matrix solution needing to reach 12.0 wt.%. Secondly, Cr is a ferrite-forming element, which shrinks the austenite region. According to the Schaeffler phase diagram, to obtain a single martensitic structure and ensure high strength, the formation of δ-ferrite or the content of retained austenite should be minimized. In this invention, the Cr equivalent Creq = Cr% + Mo% + 1.5 × Si% + 0.5 × Nb% + 5 × V% + 3Al is controlled within 15.0%. Based on thermodynamic calculations, the Cr content range is taken as 12.0% to 15.0%.
[0018] 3) Nb microalloying elements play an important role in this invention. Nb precipitates with C and N at high rolling temperatures to form Nb(C,N), which not only refines the grain size but also improves strength and toughness. Due to the precipitation of Nb(C,N) at high temperatures, the dissolved carbon content is reduced, thereby reducing Cr content. 23 C6, Cr x N y The formation temperature of chromium carbonitrides must be ensured to guarantee Cr 23 C6, Cr x N y The formation temperature is lowered below the hot stamping temperature to ensure that more Cr element is dissolved in the matrix, thereby improving corrosion resistance. Considering both toughening and cost factors, and based on thermodynamic calculations, the reasonable control range for Nb in this invention is 0.02% to 0.10%.
[0019] 4) V is another important microalloying element in this invention. V precipitates as V(C, N) at rolling or hot stamping temperatures, which can refine grains and martensitic steel laths, significantly improving strength and toughness. Similarly, the precipitation of V(C, N) reduces Cr... 23 C6, Cr x N y The formation temperature is controlled to ensure corrosion resistance. The appropriate range for V in the stainless steel of this invention is 0.05% to 0.15%.
[0020] 5) Ni is a strong austenite-forming element and can replace Ni in stainless steel, significantly reducing the amount of Ni used and offering the advantage of low cost. This invention fully utilizes the precipitation strengthening effect of Ni with microalloying elements Nb and V to improve strength, while strictly controlling the addition of excessive Ni content, because too high a Ni content will affect Cr. x N y The precipitation temperature will increase, meaning that Cr precipitation must be avoided at hot stamping temperatures. x N y This reduces the solid solution content of Cr, thereby ensuring corrosion resistance. Based on thermodynamic calculations, the reasonable control range for N is 0.01%–0.15%.
[0021] 6) Si, as a ferrite stabilizing element in stainless steel, contributes to improving strength, oxidation resistance, and corrosion resistance. It also commonly exists in stainless steel as a deoxidizer. In this invention, considering the control requirements of Creq and the need to obtain martensitic structure, the Si content is controlled at 0.05% to 0.50%.
[0022] 7) Mn is a relatively weak austenite-forming element in stainless steel, but it has a strong austenite-stabilizing effect. Furthermore, the strength of stainless steel increases with increasing Mn content. In this invention, adding a certain amount of Mn ensures austenitization and improves strength. Based on thermodynamic calculations, the reasonable control range for Mn is 0.50% to 2.0%.
[0023] 8) Ni is an important austenitizing element in stainless steel, which has a significant impact on improving strength and toughness. However, Ni is expensive. In order to maintain the low-cost competitiveness of automotive hot stamping parts and considering factors such as scrap steel smelting, the content of Ni is usually controlled within 1.00%.
[0024] 9) In this invention, Cu is a residual element brought in by scrap steel during the stainless steel smelting process. Although it contributes to the strength to a certain extent, it is not deliberately added as a strengthening element and is usually kept below 0.30%.
[0025] 10) Al is usually added as a deoxidizer in stainless steel. To ensure sufficient deoxidation in the steel of this invention and to control costs, the content of Al is generally controlled within 0.05%.
[0026] 11) P and S are impurity elements that are detrimental to the toughness of stainless steel. In principle, the lower the content, the better. Considering cost control, this invention controls the content of P and S to P≤0.02% and S≤0.010%.
[0027] The key alloy design concept of this invention is based on 1Cr 13 2Cr 13Based on this, appropriate amounts of Nb and V microalloying elements and a certain amount of N are added, and the hot stamping process is cleverly utilized to ensure high strength, toughness, and corrosion resistance. During the heating, holding, and cooling processes of hot stamping, the following measures are taken: first, to minimize the formation of δ-ferrite and ensure a fully martensitic structure to maintain high strength; second, to fully utilize the microalloying Nb and V elements to form nanoscale Nb(C,N) and V(C,N) reinforcing phases with C and N, further enhancing the strength to above 1500 MPa; and third, to solidify the Cr formed during hot rolling or cold rolling annealing. 23 C6, Cr x Chromium carbonitrides such as Ny have their solid-solid C and N atoms captured by Nb and V, thus significantly improving their corrosion resistance.
[0028] Based on the aforementioned design concept, this invention, combined with Schaeffler phase diagrams and Thermo-Calc thermodynamic calculations, addresses key phases such as austenite, ferrite, and martensite at different compositions and temperatures, as well as Nb (C, N), V (C, N), and Cr. 23 C6, Cr x N y The formation temperature and quantity of precipitated phases are calculated to establish the correspondence between chemical elements and key phases, as well as the formation temperature and quantity of precipitates, which serves as the principle for screening and controlling the content of chemical components.
[0029] To meet the needs of large-scale production involving forging and rolling hot working at temperatures above 1100℃, the steel grade of this invention needs to avoid the formation of the δ phase at high temperatures and fully utilize the strengthening and grain-refining effects of Nb (C, N). Therefore, the δ phase formation temperature and the Nb (C, N) solid solution temperature are both ≥1100℃. To ensure that Cr is present in the matrix structure during hot stamping... 23 C6, Cr x N y Complete dissolution reduces Cr element consumption, thus improving corrosion resistance. 23 C6, Cr x N y The solid solution temperature needs to be ≤950℃; in addition, in order to fully utilize the precipitation strengthening effect of V(C,N), the solidification temperature of V(C,N) needs to be higher than 870℃.
[0030] Furthermore, to address the high cost and low efficiency issues arising from large-scale trial-and-error experiments in traditional component design, this invention proposes a method for rapid component screening that integrates thermodynamic calculations and high-throughput experiments. This method is used to develop the aforementioned 1500MPa-grade corrosion-resistant stainless steel for hot-stamped automotive parts, and specifically includes the following steps:
[0031] 1) By analyzing the application scenarios and requirements of different steel grades, benchmark products were collected based on product characteristics to serve as performance optimization standards. Given the requirements for high strength and high corrosion resistance after hot stamping, the target steel grade is predominantly martensitic; therefore, 1Cr martensitic stainless steel was selected. 13 2Cr 13 Based on this, corrosion resistance is improved by microalloying with N, Nb, and V.
[0032] 2) For the composition system determined in step 1), the thermodynamic software Thermo-Calc is used to call the iron-based multi-component thermodynamic database TCFE10 to calculate the phase diagram under the relevant composition. The phase diagram data, the principle of equilibrium phase transition and other thermodynamic calculation methods and Schaeffler phase diagram are used to predict the phase composition and performance enhancement mechanism of the material under different temperature and composition conditions. The coupling between the mechanical properties and application performance of different components is evaluated, and the components of high-performance (high strength, high corrosion resistance) material are preliminarily determined.
[0033] 3) Based on step 2), the key phases that influence mechanical and application performance are identified and named characteristic parameters. Then, using the kinetic simulation software DICTRA, based on the phase diagram thermodynamic database TCFE10 and the diffusion kinetic database MOBFE5, the phase transition temperature, phase ratio, second phase precipitation temperature, and phase transition process of the material are calculated. Combined with the material's toughness mechanism and corrosion resistance mechanism, specific material composition screening criteria are provided, thereby obtaining the optimized composition range.
[0034] 4) Using the composition optimization results determined in step 3), high-throughput experiments such as smelting, hot rolling, cold rolling, and heat treatment are carried out quickly and at low cost in a small-scale vacuum induction melting furnace to obtain actual experimental data on the mechanical properties and pitting performance of hot stamping process, and further verify and optimize to obtain the final composition system and process scheme that meets the user's needs.
[0035] Compared with the prior art, the beneficial effects of the present invention are:
[0036] 1) The steel grade of the present invention not only has high strength, but also good corrosion resistance. Combined with the corresponding hot stamping forming process, it is suitable for manufacturing automotive structural parts, reinforcement parts, safety parts and other components, such as bumpers, B-pillar reinforcement parts, etc.
[0037] 2) The addition of a certain amount of nitrogen (N) element in this invention, which dissolves in the matrix, improves mechanical properties. Therefore, adding an appropriate amount of N element to this steel grade can reduce the carbon (C) content, thereby improving the corrosion resistance and weldability of martensitic stainless steel. N element shows a tendency to replace Ni in this invention, offering the advantage of low cost.
[0038] 3) The high-strength corrosion-resistant hot-stamped stainless steel of the present invention has an anti-oxidation effect during the hot stamping process, eliminating the need for Al-Si coating protection. Furthermore, the inherent corrosion resistance of the steel itself reduces the need for pickling, degreasing, phosphating, painting, and other processes during the vehicle body manufacturing process, significantly reducing costs in the production and manufacturing stage. It is a new type of green and environmentally friendly steel.
[0039] 4) The stainless steel of this invention has a tensile strength of 1500 MPa or higher and a pitting potential of ≥0.05V. SCE It has good corrosion resistance. Attached Figure Description
[0040] Figure 1 This is a SEM micrograph of the 1500MPa grade hot-stamped stainless steel of Example 1 of this application.
[0041] Figure 2 The electrochemical test curves are for the 1500MPa grade hot-stamped stainless steel of Example 1 of this application and the comparative example. Detailed Implementation
[0042] The specific embodiments of the present invention will be further described below with reference to the examples. The following examples are used to specifically illustrate the content of the present invention. These examples are only general descriptions of the content of the present invention and do not limit the content of the present invention.
[0043] The following describes an embodiment of the present application of a 1500MPa high-strength hot-stamped stainless steel sheet for automotive parts and its development method.
[0044] A 1500MPa grade corrosion-resistant stainless steel for hot-stamped automotive parts, the chemical composition of the steel by weight percentage is as follows: C: 0.05%~0.18%, Si: 0.05%~0.50%, Mn: 0.50%~2.00%, P≤0.020%, S≤0.010%, Cr: 12.0%~15.0%, V: 0.05%~0.15%, Nb: 0.02%~0.10%, Ni≤1.00%, Cu≤0.30%, Al<0.05%, N: 0.01%~0.10%, with the balance being Fe and unavoidable impurity elements such as Cu, Mg, O, Ca, etc.
[0045] The Cr equivalent (Creq) in steel, calculated as Cr% + Mo% + 1.5 × Si% + 0.5 × Nb% + 5 × V% + 3Al, should be controlled below 15.0%. The Ni equivalent (Nieq) in steel, calculated as Ni% + 30 × C% + 0.5 × Mn% + 0.3 × Cu% + 25 N% + Co%, should be controlled below 8.0%. The δ phase formation temperature in the steel should be ≥1100℃, and the Nb (C, N) solution treatment temperature should be ≥1100℃. The Cr content in the steel... 23 C6 and Cr xN y The solution solution temperature is ≤950℃. The solution solution temperature of V (C, N) in steel is higher than 870℃.
[0046] Micrographs of the high-strength, high-corrosion-resistant hot-stamped stainless steel sheet prepared by this method are shown below. Figure 1 As shown.
[0047] A method for rapid component screening using integrated thermodynamic calculations and high-throughput experimental assistance, applicable to the development of 1500MPa grade corrosion-resistant stainless steel for hot-stamped automotive parts, specifically includes the following steps:
[0048] 1) Collect experimental data and determine the range of chemical composition of the experimental steel plate.
[0049] By analyzing the application scenarios and requirements of different steel grades, a benchmark product system was collected based on product characteristics to serve as a performance optimization standard. Given the requirements for high strength and high corrosion resistance after hot stamping, the target steel grade is predominantly martensitic; therefore, martensitic stainless steel 1Cr was selected. 13 2Cr 13 Based on this, corrosion resistance is improved by microalloying with N, Nb, and V.
[0050] 2) Thermodynamic calculations, empirical formulas, and strengthening mechanism analysis determine the phase composition and strengthening component type of the system.
[0051] For the composition system determined in step 1), the thermodynamic software Thermo-Calc was used to call the iron-based multi-component thermodynamic database TCFE10 to calculate the phase diagram under the relevant composition. The phase diagram data, the principle of equilibrium phase transition and other thermodynamic calculation methods and Schaeffler phase diagram were used to predict the phase composition and performance enhancement mechanism of the material under different temperature and composition conditions. The coupling between the mechanical properties and application properties of different components was evaluated, and the components of high-performance (high strength, high corrosion resistance) material were preliminarily determined.
[0052] 3) Combine the heat treatment process with thermodynamic calculations to control characteristic parameters, thereby optimizing the selection of steel composition.
[0053] Based on step 2), the key phases that influence mechanical and application performance are identified and named characteristic parameters. Then, using the kinetic simulation software DICTRA, based on the phase diagram thermodynamic database TCFE10 and the diffusion kinetic database MOBFE5, the phase transition temperature, phase ratio, second phase precipitation temperature, and phase transition process of the material are calculated. Combined with the material's toughness mechanism and corrosion resistance mechanism, specific material composition screening criteria are provided, thereby obtaining the optimized composition range.
[0054] 4) Based on the calculation results in step 3, conduct high-throughput experiments to further verify and optimize the component range.
[0055] Using the composition optimization results determined in step 3), high-throughput experiments such as smelting, hot rolling, cold rolling, and heat treatment are carried out rapidly and at low cost in a small-scale vacuum induction melting furnace. Actual experimental data on the mechanical properties and pitting performance of hot stamping process are obtained, and the final composition system and process scheme that meet the user's needs are further verified and optimized.
[0056] The following specific embodiments further illustrate this solution.
[0057] Table 1 shows the chemical composition of the steels in Examples 1-5; Table 2 shows the formation temperatures of each critical phase calculated using the Thermo-Calc software package; Table 3 shows the pitting corrosion performance of the steels finally obtained in Examples 1-5.
[0058] Table 1 Chemical composition (wt / %) of the examples
[0059] 1 0.08 0.08 0.8 13 0.04 0.011 0.005 0.12 0.03 0.04 2 0.05 0.05 1.8 14 0.08 0.008 0.006 0.15 0.1 0.04 3 0.09 0.09 0.9 12.6 0.05 0.012 0.004 0.11 0.04 0.035 4 0.1 0.1 1 13 0.06 0.011 0.005 0.09 0.05 0.02 5 0.07 0.11 1.2 12.8 0.07 0.012 0.004 0.1 0.06 0.04 6 0.06 0.12 1.2 13.2 0.08 0.009 0.005 0.08 0.05 0.03 7 0.13 0.12 1.8 13.9 0.06 0.008 0.003 0.07 0.08 0.025 8 0.16 0.48 1.5 13.8 0.08 0.01 0.005 0.05 0.05 0.045 9 0.18 0.04 0.8 13.3 0.08 0.006 0.004 0.12 0.09 0.045 Comparative Example 0.17 0.5 0.6 13.8 - 0.008 0.004 - - 0.03
[0060] Table 2 Formation temperature (°C) of characteristic parameters in hot-stamped stainless steel
[0061]
[0062]
[0063] In the example, the components were prepared by a 1kg vacuum induction melting furnace to form an ingot, which was then hot rolled, pickled, and cold rolled to obtain a 1.5mm thick cold-rolled sheet. After that, a hot forming test was carried out. The specific parameters were: austenitizing heating temperature of 950℃, holding time of 5-6min, then transferred to a hot stamping die within 8s for stamping, holding pressure for 6-10s, and then cooling to below 150℃ before being taken out.
[0064] Table 3 Mechanical properties and pitting corrosion resistance of hot-stamped stainless steel
[0065] 1 1115 1564 5 0.08 2 1076 1501 6.0 0.10 3 1123 1640 6.5 0.07 4 1285 1665 7.2 0.08 5 1317 1719 5.9 0.09 6 1293 1698 5.5 0.1 7 1318 1754 5.0 0.07 8 1305 1738 4.5 0.06 9 1426 1786 3.0 0.05 Comparative Example 886 1350 8.5 Activated system, no pitting potential
[0066] As can be seen from the data in Tables 1-3, the technical solution adopted in this invention produces steel plates with a tensile strength ≥1500MPa and a pitting potential ≥0.05V. SCE It is a hot-stamped stainless steel with a tensile strength of 1500MPa and good corrosion resistance.
Claims
1. A 1500MPa grade corrosion-resistant stainless steel for hot-stamped automotive parts, characterized in that, The chemical composition of the steel, by weight percentage, is as follows: C: 0.06%~0.20%, Si: 0.05%~0.50%, Mn: 0.50%~2.00%, P≤0.020%, S≤0.010%, Cr: 12.0%~14.0%, V: 0.05%~0.09%, Nb: 0.02%~0.09%, Ni≤1.00%, Cu≤0.30%, Al<0.05%, N: 0.01%~0.10%, with the balance being Fe and unavoidable impurity elements; The Cr equivalent in steel, Creq = Cr% + Mo% + 1.5 × Si% + 0.5 × Nb% + 5 × V% + 3Al, should be controlled within 15.0%. The Ni equivalent in steel, Nieq = Ni% + 30 × C% + 0.5 × Mn% + 0.3 × Cu% + 25 N% + Co%, should be controlled within 8.0%. The δ phase formation temperature in the steel is ≥1100℃, and the Nb (C, N) solution solution temperature is ≥1100℃; Cr in steel 23 C6 and Cr x N y The solution treatment temperature is ≤950℃; The solidification temperature of V (C, N) in steel is above 870℃; The stainless steel plate has a tensile strength ≥1500MPa and a pitting potential ≥0.05V. SCE .
2. A method for rapid component screening aided by integrated thermodynamic calculations and high-throughput experiments, characterized in that, This method is used to develop 1500MPa grade corrosion-resistant stainless steel for hot-stamped automotive parts as described in claim 1, and specifically includes the following steps: 1) By analyzing the application scenarios and requirements of steel grades, benchmark product systems were collected based on product characteristics to serve as performance optimization benchmarks; the target steel grade is mainly martensitic, with 1Cr martensitic stainless steel as the primary example. 13 2Cr 13 Based on this, corrosion resistance is improved through microalloying with N, Nb, and V; 2) For the composition system determined in step 1), the thermodynamic software Thermo-Calc was used to call the iron-based multi-component thermodynamic database TCFE10 to calculate the phase diagram under the relevant composition; the thermodynamic calculation method and Schaeffler phase diagram were used to predict the phase composition and performance enhancement mechanism of the material under different temperature and composition conditions, evaluate the coupling between the mechanical properties and application properties of different components, and preliminarily determine the material components. 3) Based on step 2), the key phases that influence mechanical and application performance are identified and named as characteristic parameters. Then, using the kinetic simulation software DICTRA, based on the phase diagram thermodynamic database TCFE10 and the diffusion kinetic database MOBFE5, the phase transition temperature, phase ratio, second phase precipitation temperature, and phase transition process of the material are calculated. Combined with the material's toughness mechanism and corrosion resistance mechanism, specific material composition screening criteria are provided to obtain the optimized composition range. 4) Using the composition optimization results determined in step 3), high-throughput experiments were conducted in a vacuum induction melting furnace to carry out smelting, hot rolling, cold rolling, and heat treatment. Actual experimental data on the mechanical properties and pitting properties of the hot stamping process were obtained, and the final composition system was further verified and optimized.
Citation Information
Patent Citations
Steel for manufacturing a component by hot forming and use of the component
CN110382723A
Hot stamping high strength steel automobile body covering part and manufacturing method and system thereof
CN109433960A